Treatment of adriamycin-induced nephropathy with erythropoietin and G-CSF - Andrade, Luís Gustavo Modelli de [UNESP]; Marlene Viero, Rosa [UNESP]; Cordeiro de Carvalho, Maria Fernanda [UNESP] (SAGE Publications, 2013)
Background: Granulocyte colony-stimulating factor (G-CSF) and Erythropoietin (EPO) are known to stimulate the growth and differentiation of progenitor cells to prevent acute renal injury. This study aimed to assess the use of growth factors to mobilize stem cell in a mouse model of adriamycin-induced chronic kidney disease. Methods: All animals were injected with adriamycin for kidney injury and allocated into three treatment groups (G-CSF, EPO and G-CSF + EPO), and a control group (adriamycin alone). Results: Number of atrophic sites, glomerulosclerosis rate and interstitial fibrosis severity score were assessed in all groups. In all treatment groups, histologic parameters did not significantly differ, but were lower than in the control group (P<.001). Scal and CD34 expressions among treatment groups showed no statistically significant difference, but were higher than in the control group (P<.0001). CD105 expression was higher in EPO and G+EPO as compared to G-CSF and the control group (P<.0001), with no statistically significant difference between the latter two groups (P = NS). Conclusion: G-CSF and EPO had a histologic protective effect, while treatment with EPO + G-CSF had no additive effects in a model of adriamycin-induced chronic kidney disease. © 2013 Societá Italiana di Nefrologia.
Keywords: Adriamycin; Erythropoietin; G-CSF; Mobilization; Nephropathy; Stem cell; alfaepoetina; ataxin 1; CD34 antigen; doxorubicin; endoglin; recombinant erythropoietin; recombinant granulocyte colony stimulating factor; unclassified drug; animal experiment; animal model; animal tissue; atrophy; chronic kidney disease; controlled study; disease severity; drug effect; glomerulosclerosis; histopathology; kidney fibrosis; male; mouse; nonhuman; protein expression; renal protection; scoring system; stem cell mobilization